Media And Mass Shootings: Second Level Agenda Setting In CNN News Coverage Of The Columbine And Parkland Mass Shootings - Hume, Hannah E. (2020)
Through discourse analysis, this article seeks to compare the cable news coverage of the Columbine High School school shooting and the Marjory Stoneman Douglas High School school shooting using second-level agenda setting theory, with CNN broadcast transcripts as the unit of analysis. The research showed that the shooter was the dominant shaping force in the creation of the agenda for cable news coverage in both school shooting events